Re-examination and Analyzing the Principality of Existence of Avicenna: A Case Study of the Phrases in "al-Mubāḥathāt"(The Discussions) - Mohammad Tashakori Abghad; GholamAli Moghaddam (آموزه‌‌های فلسفه اسلامي)
The issue of the excess and primacy of existence and essence is one of the most important philosophical discussions, serving as a bridge from general skepticism to specific and more specific skepticism. Although this topic was explicitly raised as an independent issue within the Isfahan philosophical school, its roots can be traced throughout the history of philosophy. Therefore, the emergence and development of this issue should be regarded as a product of the philosophical discourse prior to the Isfahan school. As a result, the foundations and arguments for the principality of existence can be found in the thoughts of earlier philosophers as well. Ibn Sina (Avicenna) is considered one of the philosophers who explicitly addressed the excess of existence and essence, while implicitly discussing the principality of existence. Given that some scholars have classified Ibn Sina as an advocate of "principality of existence," others have attributed to him the view of "principality of essence," and still others have leaned toward the notion of "suspension" (waqf) regarding his view, the central research question is whether one can find in Ibn Sina's "al-Mubāḥathāt"(The Discussions) any allusions close to an explicit declaration of the principality of existence, thus strengthening the attribution of existential principality to him and considering later existentialists as continuers of his intellectual path. The authors of this study have aimed to examine this hypothesis in a descriptive-analytical manner. By analyzing Ibn Sina's statements in "al-Mubāḥathāt" they try to demonstrate a comprehensive and systematic view of Ibn Sina's principles, perspectives, and statements fully supports this claim, thus enabling the assertion of the "Avicennan principality of existence."